Isolating membrane, battery monomer, battery and electric device
By using porous substrates and ferroelectric coating isolation films in the battery, the battery reliability and service life problems caused by dendrite growth are solved, and higher battery reliability and performance are achieved.
Patent Information
- Application Number
- CN202311276950.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-28
AI Technical Summary
During the charging and discharging process of existing batteries, the growth of dendrites leads to a decrease in battery reliability and service life, and it is difficult to effectively alleviate them.
An isolation film comprising a porous substrate and a ferroelectric coating located on at least one surface of the porous substrate is used. The ferroelectric coating consists of inorganic ferroelectric bodies and ferroelectric polymers. The content of beta-phase polyvinylidene fluoride in the ferroelectric polymer is greater than or equal to 60% to slow down the growth of dendrites in the vertical electrode plate direction.
Effectively slow down the growth of dendrites, reduce the occurrence of internal short circuits of the battery, and improve the reliability, Coulomb efficiency and rate performance of the battery.
Smart Images

Figure CN119725977A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to an isolation film, a battery cell, a battery and an electrical device. Background Art
[0002] In recent years, batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in consumer electronics, power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. With the application and promotion of batteries, their reliability has received more and more attention. During the battery charging and discharging process, the dendrite problem on the negative electrode is one of the important reasons affecting the reliability and service life of the battery. How to slow down the growth of dendrites without affecting the performance of the battery is a technical problem that needs to be solved urgently. The above statements are only used to provide background technical information related to this application and do not necessarily constitute prior art. Summary of the invention
[0003] The present application provides an isolation membrane, a battery cell, a battery and an electrical device. The isolation membrane can slow down the continuous growth of dendrites in the direction perpendicular to the pole piece, reduce the internal short circuit of the battery, improve the reliability of the battery, and also improve the coulombic efficiency and rate performance of the battery.
[0004] The first aspect of the present application provides an isolation membrane, comprising a porous substrate and a ferroelectric coating located on at least one surface of the porous substrate. The ferroelectric coating comprises a ferroelectric material, the ferroelectric material comprises an inorganic ferroelectric and a ferroelectric polymer, the ferroelectric polymer comprises polyvinylidene fluoride and its copolymer, the ferroelectric polymer comprises β-phase polyvinylidene fluoride, and the content of β-phase polyvinylidene fluoride in the ferroelectric polymer is greater than or equal to 60%.
[0005] The ferroelectric polymer provided in the embodiment of the present application can not only act as a binder, but also have a higher dielectric constant ε r , which can also slow down the continuous growth of dendrites in the direction perpendicular to the pole piece and reduce the internal short circuit of the battery. When applied to batteries, it can improve the reliability, coulomb efficiency and rate performance of the battery.
[0006] In any embodiment, the content of β-phase polyvinylidene fluoride in the ferroelectric polymer is greater than or equal to 80%, and can be optionally greater than or equal to 90%.
[0007] This can further slow down the continuous growth of dendrites in the direction perpendicular to the electrode, reduce internal short circuits in the battery, and improve the coulombic efficiency and rate performance of the battery.
[0008] In any embodiment, the dielectric constant ε of the ferroelectric coating is r Greater than the dielectric constant ε of the inorganic ferroelectric r Optionally, the dielectric constant ε of the ferroelectric coating isr The dielectric constant ε of the inorganic ferroelectric r The ratio is greater than or equal to 1.6, and can be optionally greater than or equal to 2.0.
[0009] This can further slow down the continuous growth of dendrites in the direction perpendicular to the electrode, reduce internal short circuits in the battery, and improve the coulombic efficiency and rate performance of the battery.
[0010] In any embodiment, the dielectric constant ε of the inorganic ferroelectric r Greater than the dielectric constant ε of the ferroelectric polymer r .
[0011] In any embodiment, the dielectric constant ε of the inorganic ferroelectric r It is 200-8000, and can be optionally 2000-6000.
[0012] In any embodiment, the dielectric constant ε of the ferroelectric polymer is r 5-100, optional 8-70.
[0013] In any embodiment, at least a portion of the ferroelectric polymer is located on at least a portion of the surface of the inorganic ferroelectric.
[0014] When the ferroelectric polymer is located on at least part of the surface of the inorganic ferroelectric, the probability of the ferroelectric coating losing ferroelectricity due to the ferroelectric-paraelectric transition of the inorganic ferroelectric during the preparation of the isolation film can be further reduced, thereby better slowing down the continuous growth of dendrites in the direction perpendicular to the pole piece. In addition, it also helps to improve the coulombic efficiency of the battery. When the ferroelectric polymer is located on at least part of the surface of the inorganic ferroelectric, it also helps to reduce the dielectric constant ε of the ferroelectric coating. r The dielectric constant ε is larger than that of inorganic ferroelectrics. r , which is larger than the dielectric constant ε of the ferroelectric polymer r .
[0015] In any embodiment, the weight content of the inorganic ferroelectric in the ferroelectric material is 80%-99%, and optionally 85%-95%.
[0016] In any embodiment, the weight content of the ferroelectric polymer in the ferroelectric material is 1%-20%, and optionally 5%-15%.
[0017] By adjusting the weight content of the inorganic ferroelectric and the ferroelectric polymer in the ferroelectric material within the above range, the dielectric constant ε of the ferroelectric coating can be increased. r , so that the dielectric constant ε of the ferroelectric coating r The dielectric constant ε is larger than that of inorganic ferroelectrics. r , which is larger than the dielectric constant ε of the ferroelectric polymer r, which can better slow down the continuous growth of dendrites in the direction perpendicular to the electrode, reduce internal short circuits in the battery, and improve battery reliability and Coulomb efficiency; in addition, it can also increase the adhesion between the ferroelectric coating and the porous structure.
[0018] In any embodiment, the Curie point temperature of the ferroelectric polymer is 150°C-250°C, and optionally 160°C-200°C.
[0019] In any embodiment, the remanent polarization intensity of the ferroelectric polymer is 10 mC / m 2 -1000mC / m 2 , optional 20mC / m 2 -800mC / m 2 .
[0020] In any embodiment, the weight average molecular weight of the ferroelectric polymer is 200,000-800,000, and can be optionally 400,000-650,000.
[0021] The weight average molecular weight of the ferroelectric polymer is within the above range, which can make the ferroelectric polymer have suitable crystallinity, suitable Curie point temperature, and high dielectric constant ε r , and can also make the ferroelectric polymer have suitable viscosity.
[0022] In any embodiment, the melting temperature of the ferroelectric polymer is 140°C-220°C, optionally 143°C-200°C.
[0023] The melting point of the ferroelectric polymer is within the above range, which can make the ferroelectric polymer have suitable crystallinity, suitable Curie point temperature, and higher dielectric constant ε r , and can also make the ferroelectric polymer have suitable viscosity.
[0024] In any embodiment, the crystallinity of the ferroelectric polymer is greater than or equal to 45%, and can be 45%-68%. When the crystallinity of the ferroelectric polymer is within the above range, the thermal shrinkage of the isolation film can be reduced and the mechanical strength of the isolation film can be improved.
[0025] In any embodiment, the Curie point temperature of the inorganic ferroelectric is 110°C-150°C, and can be optionally 120°C-140°C.
[0026] In any embodiment, the ferroelectric polymer includes one or more of polyvinylidene fluoride, a copolymer of a vinylidene fluoride monomer and other monomers.
[0027] Optionally, the other monomers include one or more of trifluoroethylene, chlorotrifluoroethylene, fluorinated acetylene, and hexafluoropropylene.
[0028] Optionally, the copolymer of the vinylidene fluoride monomer and other monomers includes one or more of vinylidene fluoride-trifluoroethylene copolymer, vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene copolymer, vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene-fluorinated acetylene copolymer, and vinylidene fluoride-hexafluoropropylene copolymer.
[0029] In any embodiment, the inorganic ferroelectric includes one or more of a perovskite type, a tungsten bronze type, a bismuth layered type, a pyrochlore type, a niobate type, and a lead barium lithium niobate.
[0030] In any embodiment, the volume distribution particle size Dv50 of the inorganic ferroelectric is 0.05 μm-5 μm, and can be optionally 0.1 μm-1 μm.
[0031] When the volume distribution particle size Dv50 of the inorganic ferroelectric is within the above range, the ferroelectric coating slurry can have a suitable viscosity, which is easy to coat and can improve the uniformity and consistency of the ferroelectric coating; it can also increase the adhesion between the ferroelectric coating and the porous structure and reduce the "powder falling" phenomenon; in addition, it can also reduce the pore blocking problem and improve the air permeability and ion transmission properties of the isolation membrane.
[0032] In any embodiment, the volume distribution particle size Dv50 of the ferroelectric polymer is 10 nm-150 nm, and can be optionally 15 nm-50 nm.
[0033] In any embodiment, the thickness of the ferroelectric coating is 1 μm-3.5 μm, and can be 1.5 μm-3 μm. Thus, the battery can have high reliability, high coulombic efficiency and good rate performance.
[0034] In any embodiment, the surface density of the ferroelectric coating is 2.5 g / m 2 -15g / m 2 , optional 3g / m 2 -12g / m 2 This allows the battery to have high reliability, high coulombic efficiency and good rate performance.
[0035] In any embodiment, the ferroelectric coating further comprises a dispersant and / or a thickener,
[0036] In any embodiment, the dispersant includes one or more of hydrolyzed polymaleic anhydride, polyacrylic acid, acrylic acid block copolymer, polyester block copolymer, polyethylene glycol type polyol, polyethylene imine, and their respective derivatives.
[0037] In any embodiment, the ratio of the total weight of the ferroelectric material to the weight of the dispersant is 1:(0.01-0.02), and can be optionally 1:(0.010-0.015).
[0038] An appropriate amount of dispersant can make the ferroelectric coating slurry dispersed evenly, facilitate coating, and also help to increase the film weight of the ferroelectric coating.
[0039] In any embodiment, the thickener includes one or more of sodium hydroxymethylcellulose, methylcellulose, hydroxyethylcellulose, hydroxypropyl methylcellulose, polyacrylate, polyurethane, and polyether.
[0040] In any embodiment, the ratio of the total weight of the ferroelectric material to the weight of the thickener is 1:(0.01-0.02), and can be optionally 1:(0.010-0.015).
[0041] An appropriate amount of thickener can improve the stability of the ferroelectric coating slurry, facilitate coating, and also help to increase the film weight of the ferroelectric coating.
[0042] In any embodiment, the ferroelectric coating is located on one surface of the porous substrate, and a ceramic coating is disposed on the other surface of the porous substrate. When used in a battery, the ferroelectric coating faces the negative electrode, and the ceramic coating faces the positive electrode.
[0043] In any embodiment, the thickness of the porous substrate is 4 μm-15 μm, and optionally 5 μm-10 μm.
[0044] In any embodiment, the porous substrate includes one or more of polyolefins, halogenated polyolefins, polyamides, polyesters, and their respective derivatives.
[0045] A second aspect of the present application provides a battery cell, which includes the isolation membrane of the first aspect of the present application.
[0046] A third aspect of the present application provides a battery, which includes the battery cell of the third aspect of the present application.
[0047] A fourth aspect of the present application provides an electrical device, which includes the battery of the third aspect of the present application.
[0048] The electric device of the present application includes the battery provided by the present application, and thus has at least the same advantages as the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0050] Figure 1 A schematic diagram showing a battery cell provided by some embodiments of the present application.
[0051] Figure 2 A schematic diagram of an exploded view of a battery cell provided by some embodiments of the present application is shown.
[0052] Figure 3 A schematic diagram of a battery module provided in some embodiments of the present application is shown.
[0053] Figure 4 A schematic diagram of a battery pack provided in some embodiments of the present application is shown.
[0054] Figure 5 yes Figure 4 An exploded diagram of the battery pack is shown.
[0055] Figure 6 A schematic diagram showing an isolation membrane provided by some embodiments of the present application.
[0056] Figure 7 Schematic diagrams showing isolation membranes provided in other embodiments of the present application.
[0057] Figure 8 Schematic diagrams showing isolation membranes provided in some further embodiments of the present application.
[0058] Fig. 9 A schematic diagram of an electrical device provided in some embodiments of the present application is shown.
[0059] Fig.10 A scanning electron microscope (SEM) image of the isolation film prepared in Example 1 is shown.
[0060] In the drawings, the drawings may not be drawn according to the actual scale. The reference numerals are as follows: 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 battery, 51 housing, 52 electrode assembly, 53 cover plate, 10 separator, 101 porous substrate, 102 ferroelectric coating, 103 second coating. DETAILED DESCRIPTION
[0061] Hereinafter, the embodiments of the isolation membrane, battery cell, battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0062] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0063] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0064] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0065] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0066] In the present application, the terms "plurality" and "multiple" refer to two or more.
[0067] In the description of the embodiments of the present application, unless otherwise specified, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or that the first and second features are in indirect contact through an intermediate medium. Furthermore, a first feature being “above”, “above”, or “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, or “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0068] Unless otherwise specified, the terms used in this application have the commonly understood meanings that are commonly understood by those skilled in the art.
[0069] Unless otherwise specified, the values of the parameters mentioned in this application can be measured by various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise specified, the test temperature of each parameter is 25°C.
[0070] The Dv50 of a material is well known in the art and can be measured using instruments and methods known in the art. For example, it can be conveniently measured using a laser particle size analyzer (such as Malvern Mastersizer 3000) in accordance with GB / T 19077-2016. The physical definition of Dv50 is the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%.
[0071] The battery mentioned in the embodiments of the present application may be a single physical module including one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in the present application may include a battery cell, a battery module or a battery pack.
[0072] A battery cell is the smallest unit of a battery, which can independently realize the functions of charging and discharging. The battery cell can be cylindrical, rectangular or in other shapes, etc., which is not limited in the present application. Figure 1 The battery cell 5 is a rectangular parallelepiped structure as an example.
[0073] When there are multiple battery cells, the multiple battery cells are connected in series, in parallel, or in mixed connection through a busbar. In some embodiments, the battery may be a battery module; when there are multiple battery cells, the multiple battery cells are arranged and fixed to form a battery module. In some embodiments, the battery may be a battery pack, which includes a case and battery cells, and the battery cells or battery modules are accommodated in the case. In some embodiments, the case may serve as part of the chassis structure of the vehicle. For example, part of the case may become at least a part of the floor of the vehicle, or part of the case may become at least a part of the crossbeam and longitudinal beam of the vehicle.
[0074] In some embodiments, the battery may be an energy storage device, which includes an energy storage container, an energy storage cabinet, and the like.
[0075] A battery cell generally includes an electrode assembly and an electrolyte. The electrode assembly may be a wound structure or a laminated structure, which is not limited in the present application.
[0076] The battery cell may also include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte. The outer package may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).
[0077] In some embodiments, Figure 2 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The electrode assembly 52 is encapsulated in the receiving cavity. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.
[0078] In some embodiments, battery cells may be assembled into a battery module. The battery module may contain multiple battery cells, and the specific number may be adjusted according to the application and capacity of the battery module. Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0079] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0080] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0081] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5As shown, the battery pack 1 may include a box body and a plurality of battery modules 4 disposed in the box body. The box body includes an upper box body 2 and a lower box body 3, and the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the box body in any manner.
[0082] The battery cells provided in the embodiments of the present application may include lithium battery cells and sodium battery cells, for example, lithium ion battery cells, lithium metal battery cells, negative electrode-free lithium metal battery cells, sodium ion battery cells, sodium metal battery cells, negative electrode-free sodium metal battery cells, etc.
[0083] A negative electrode-free battery cell generally refers to a battery cell that is formed by not actively setting a negative electrode active material layer on the negative electrode side during the manufacturing process of the battery cell, for example, in the manufacturing process of the battery cell, a layer is not set at the negative electrode through processes such as coating or deposition, or a negative electrode active material layer is formed by a carbonaceous active material layer. During the first charge, the ions obtain electrons on the negative electrode side and deposit on the surface of the negative electrode current collector to form a metal. During discharge, the metal can be converted into ions and return to the positive electrode to achieve cyclic charge and discharge. Compared with other battery cells, a negative electrode-free battery cell can obtain a higher energy density because it does not have a negative electrode active material layer. In some embodiments, in order to improve the performance of the battery cell, some conventional substances that can be used as negative electrode active materials, such as carbon materials, can also be set on the negative electrode side of the negative electrode-free battery cell. Although these substances have a certain capacity, due to their low content and not being used as the main negative electrode active material in the battery cell, the battery cell thus constructed can still be regarded as a negative electrode-free battery cell. The CB (Cell Balance) value of a battery cell without a negative electrode is usually very small. For example, in some embodiments, the CB value of a battery cell without a negative electrode may be less than or equal to 0.1. The CB value is the unit area capacity of the negative electrode in the battery cell divided by the unit area capacity of the positive electrode. Since the battery cell without a negative electrode does not contain or contains only a small amount of negative electrode active material, the unit area capacity of the negative electrode is small, and thus the CB value is very small, for example, usually less than or equal to 0.1.
[0084] As an important component of battery cells, the performance of the separator is crucial to the performance of the battery. The separator is located between the positive electrode and the negative electrode, and its main function is to prevent short circuits. The separators currently used in commercial batteries are usually porous membranes of polyolefins (such as polyethylene, polypropylene, etc.). However, the electrolyte wettability and thermal stability of such separators are poor. In addition, as the number of battery charge and discharge times increases, some dendrites will form at the negative electrode interface. The continued growth of dendrites will pierce the separator, causing internal short circuits, and in severe cases, even fires, explosions and other safety accidents.
[0085] In addition, a ceramic coating is usually provided on the commonly used isolation membrane, but the ceramic coating usually acts as a physical barrier. As the number of charge and discharge times of the battery increases, there is still a possibility that dendrites will grow along the pores of the ceramic coating and pierce the isolation membrane, and thus the problem of dendrite growth cannot be effectively alleviated.
[0086] Therefore, developing an isolation membrane with good thermal stability, excellent electrolyte wettability and the ability to alleviate dendrite growth is a technical problem that needs to be urgently solved in this field.
[0087] Figure 6 A schematic diagram showing an isolation membrane provided by some embodiments of the present application. Figure 7 Schematic diagrams showing isolation membranes provided in other embodiments of the present application. Figure 8 Schematic diagrams showing isolation membranes provided in some further embodiments of the present application.
[0088] like Figures 6 to 8 As shown, the isolation film 10 includes a porous substrate 101 and a ferroelectric coating 102 located on at least one surface of the porous substrate 101. The ferroelectric coating 102 includes a ferroelectric material, the ferroelectric material includes an inorganic ferroelectric and a ferroelectric polymer, and the ferroelectric polymer includes polyvinylidene fluoride and its copolymer. The ferroelectric polymer includes β-phase polyvinylidene fluoride, and the content of β-phase polyvinylidene fluoride in the ferroelectric polymer is greater than or equal to 60%.
[0089] The porous substrate is highly hydrophobic, and the electrolyte usually uses a polar solvent, which results in poor electrolyte wettability of the porous substrate and high ion transfer impedance. The ferroelectric coating introduced in the isolation membrane provided in the embodiment of the present application includes an inorganic ferroelectric and a ferroelectric polymer, which can improve the compatibility of the isolation membrane with the electrolyte, improve the wetting characteristics of the isolation membrane to the electrolyte, and reduce the ion transfer impedance of the isolation membrane, thereby helping the battery to have good cycle performance and rate performance. In addition, the ferroelectric coating introduced in the isolation membrane provided in the embodiment of the present application can also improve the heat resistance and mechanical strength of the isolation membrane.
[0090] During the reduction and deposition of ions at the negative electrode, stress will accumulate due to local volume expansion. Inorganic ferroelectrics have high dielectric constants and spontaneous polarization. Under the action of stress, inorganic ferroelectrics are affected by the electric field and spontaneously polarize. As a result, the positive charge center of the inorganic ferroelectric moves toward the electron gathering area of the negative electrode, thereby wrapping the electron gathering area. At the same time, since the positive charge center of the inorganic ferroelectric is positively charged, it repels the positively charged ions on the surface of the dendrite, thereby changing the growth direction of the dendrite, slowing down the continuous growth of the dendrite in the direction perpendicular to the pole piece, and reducing the internal short circuit of the battery. However, the Curie point temperature of inorganic ferroelectrics is usually low. During the preparation of the isolation film, ferroelectric-paraelectric transition may occur, causing the ferroelectric coating to lose its ferroelectricity and cause failure. In addition, inorganic ferroelectrics usually have problems such as uneven distribution and low content in the isolation film coating.
[0091] Typical representatives of polyvinylidene fluoride are α-phase polyvinylidene fluoride and β-phase polyvinylidene fluoride. α-phase polyvinylidene fluoride is a monoclinic system with TGTG arrangement, and its net dipole moment is zero and has no apparent polarity; β-phase polyvinylidene fluoride is an orthorhombic system with TTTT all-trans arrangement, and has a large spontaneous polarization intensity, and is easily polarized under an external electric field and exhibits excellent dielectric properties. At present, the binder used in the isolation film coating is mostly α-phase polyvinylidene fluoride, which does not have ferroelectricity.
[0092] The ferroelectric polymer in the ferroelectric coating of the isolation film provided in the embodiment of the present application includes β-phase polyvinylidene fluoride, and the content of β-phase polyvinylidene fluoride in the ferroelectric polymer is greater than or equal to 60%. Therefore, the ferroelectric polymer provided in the embodiment of the present application can not only act as a binder, but also have a higher dielectric constant ε r , which can also slow down the continuous growth of dendrites in the direction perpendicular to the pole piece and reduce the internal short circuit of the battery.
[0093] Placing the ferroelectric polymer together with the inorganic ferroelectric in the ferroelectric coating can also reduce the probability of the ferroelectric coating losing ferroelectricity due to the ferroelectric-paraelectric transition of the inorganic ferroelectric in the preparation of the isolation film, thereby playing a long-term role in slowing down the continuous growth of dendrites in the direction perpendicular to the pole piece. In addition, "dead lithium" and "dead sodium" may also be generated during the growth of dendrites, which will greatly reduce the capacity and coulombic efficiency of the battery. Therefore, the isolation film provided in the embodiment of the present application can also play a role in improving the coulombic efficiency of the battery, especially it can improve the coulombic efficiency of the battery at high rates.
[0094] Therefore, the isolation membrane provided in the embodiment of the present application can slow down the growth of dendrites, and can also have good electrolyte wettability, low ion transfer impedance, low thermal shrinkage and high mechanical strength. When used in batteries, it can improve the reliability, coulombic efficiency and rate performance of the battery.
[0095] In some embodiments, the content of β-phase polyvinylidene fluoride in the ferroelectric polymer may be greater than or equal to 80%, and may be greater than or equal to 90%, thereby further slowing down the continuous growth of dendrites in the direction perpendicular to the pole piece, reducing the internal short circuit of the battery, and improving the coulombic efficiency and rate performance of the battery.
[0096] In some embodiments, the ferroelectric polymer may further contain a small amount of α-phase polyvinylidene fluoride and / or γ-phase polyvinylidene fluoride.
[0097] Optionally, the content of α-phase polyvinylidene fluoride in the ferroelectric polymer may be less than or equal to 20%.
[0098] Optionally, the content of γ-phase polyvinylidene fluoride in the ferroelectric polymer may be less than or equal to 10%.
[0099] The contents of β-phase polyvinylidene fluoride, α-phase polyvinylidene fluoride and γ-phase polyvinylidene fluoride in the ferroelectric polymer can be calculated by FTIR infrared absorption spectrum.
[0100]
[0101] F a =100%-F (β,γ)
[0102]
[0103]
[0104] F α It represents the content of α phase in ferroelectric polymer.
[0105] F β It represents the content of β phase in ferroelectric polymer.
[0106] F γ It represents the content of γ phase in ferroelectric polymer.
[0107] A m Indicates the peak intensity of the absorption peak at different wavelengths m. The peak intensity of each absorption peak can be expressed by the integrated area of each absorption peak.
[0108] K m Represents the absorption coefficient of the absorption peak at different wavelengths m.
[0109] In some embodiments, the dielectric constant ε of the ferroelectric coating is r Greater than the dielectric constant ε of inorganic ferroelectrics r .
[0110] Optionally, the dielectric constant ε of the ferroelectric coating r The dielectric constant ε of inorganic ferroelectrics r The ratio may be greater than or equal to 1.6, and may be more preferably greater than or equal to 2.0.
[0111] The dielectric constant ε of the ferroelectric coating of the isolation film provided in the embodiment of the present application is r Greater than the dielectric constant ε of inorganic ferroelectrics r This can further slow down the continuous growth of dendrites in the direction perpendicular to the electrode, reduce internal short circuits in the battery, improve battery reliability, and improve the coulombic efficiency and rate performance of the battery.
[0112] In some embodiments, the dielectric constant ε of the inorganic ferroelectric is r Greater than the dielectric constant ε of the ferroelectric polymer r .
[0113] In some embodiments, the dielectric constant ε of the inorganic ferroelectric is r It can be 200-8000, optionally 2000-6000.
[0114] In some embodiments, the dielectric constant ε of the ferroelectric polymer is r It can be 5-100, optionally 8-70.
[0115] The dielectric constant ε of the above ferroelectric coating is r , the dielectric constant ε of inorganic ferroelectrics r , the dielectric constant ε of ferroelectric polymer r The test can be performed as follows: at 25°C, take an appropriate amount of sample powder, cover both sides with aluminum foil, place in a mold, and use a powder tablet press to press into a disc with a pressure of 2 MPa and a holding time of 2 min; after the pressing is completed, remove the sample disc and use a precision digital bridge instrument to measure the dielectric constant ε in the frequency range of 20 Hz-2 MHz. r test.
[0116] The dielectric constant mentioned in this application is the relative dielectric constant ε r .
[0117] In testing the dielectric constant ε of ferroelectric coatings r When the isolation film is prepared, sampling and analysis can be performed, or a suitable amount of ferroelectric coating powder can be obtained from the finished isolation film after drying, for example, by scraping powder and sampling to obtain a suitable amount of ferroelectric coating powder.
[0118] By adjusting the distribution morphology, weight content, particle size of the inorganic ferroelectric and ferroelectric polymer in the ferroelectric coating, as well as the content of the β phase in the ferroelectric polymer, the inorganic ferroelectric and ferroelectric polymer can play a synergistic role and the dielectric constant ε of the ferroelectric coating can be increased. r The dielectric constant ε is larger than that of inorganic ferroelectrics. r , which is larger than the dielectric constant ε of the ferroelectric polymer r .
[0119] In some embodiments, at least part of the ferroelectric polymer in the ferroelectric coating is located on at least part of the surface of the inorganic ferroelectric. When the ferroelectric polymer is located on at least part of the surface of the inorganic ferroelectric, the probability of the ferroelectric coating losing ferroelectricity due to the ferroelectric-paraelectric transition of the inorganic ferroelectric in the preparation of the isolation film can be further reduced, thereby better slowing down the continuous growth of dendrites in the direction perpendicular to the pole piece. In addition, it also helps to improve the coulombic efficiency of the battery. When the ferroelectric polymer is located on at least part of the surface of the inorganic ferroelectric, it also helps to reduce the dielectric constant ε of the ferroelectric coating. r The dielectric constant ε is larger than that of inorganic ferroelectrics. r , which is larger than the dielectric constant ε of the ferroelectric polymer r .
[0120] In some embodiments, the weight content of the inorganic ferroelectric in the ferroelectric material may be 80%-99%, and optionally 85%-95%.
[0121] In some embodiments, the weight content of the ferroelectric polymer in the ferroelectric material may be 1%-20%, and optionally 5%-15%.
[0122] By adjusting the weight content of the inorganic ferroelectric and the ferroelectric polymer in the ferroelectric material within the above range, the dielectric constant ε of the ferroelectric coating can be increased. r , so that the dielectric constant ε of the ferroelectric coating r The dielectric constant ε is larger than that of inorganic ferroelectrics. r , which is larger than the dielectric constant ε of the ferroelectric polymer r , which can better slow down the continuous growth of dendrites in the direction perpendicular to the electrode, reduce internal short circuits in the battery, and improve battery reliability and Coulomb efficiency; in addition, it can also increase the adhesion between the ferroelectric coating and the porous structure.
[0123] In some embodiments, the Curie point temperature of the ferroelectric polymer may be 150°C-250°C, optionally 160°C-200°C.
[0124] In some embodiments, the remanent polarization of the ferroelectric polymer may be 10 mC / m 2 -1000mC / m 2 , optional 20mC / m 2 -800mC / m 2 .
[0125] In some embodiments, the weight average molecular weight of the ferroelectric polymer may be 200,000-800,000, and may be 400,000-650,000.
[0126] The weight average molecular weight of the ferroelectric polymer is within the above range, which can make the ferroelectric polymer have suitable crystallinity, suitable Curie point temperature, and high dielectric constant ε r , and can also make the ferroelectric polymer have suitable viscosity.
[0127] The weight average molecular weight of the ferroelectric polymer has a well-known meaning in the art and can be measured by methods known in the art, for example, by gel permeation chromatography (GPC).
[0128] In some embodiments, the melting temperature of the ferroelectric polymer may be 140°C-220°C, optionally 143°C-200°C.
[0129] The melting point of the ferroelectric polymer is within the above range, which can make the ferroelectric polymer have suitable crystallinity, suitable Curie point temperature, and higher dielectric constant ε r, and can also make the ferroelectric polymer have suitable viscosity.
[0130] The melting temperature of the ferroelectric polymer can be tested by differential scanning calorimetry (DSC). The test temperature range can be 25° C. to 400° C., and the heating rate can be 10° C. / min.
[0131] In some embodiments, the crystallinity of the ferroelectric polymer may be greater than or equal to 45%, and may be 45%-68%. When the crystallinity of the ferroelectric polymer is within the above range, the thermal shrinkage of the isolation film may be reduced and the mechanical strength of the isolation film may be improved.
[0132] In some embodiments, the ferroelectric polymer may include one or more of polyvinylidene fluoride (ie, homopolymer of vinylidene fluoride VDF monomer, abbreviated as PVDF), and copolymers of vinylidene fluoride monomer and other monomers.
[0133] By introducing other monomers into the VDF crystal region, the large-sized ferroelectric domains can be divided into nano-sized ones. The nano-ferroelectric domains are easy to respond to changes in the external electric field, thus showing a unique relaxor ferroelectric behavior, which can further increase the dielectric constant ε of the ferroelectric polymer. r Further improvement and further reduction of dielectric loss.
[0134] Alternatively, other monomers may include, but are not limited to, one or more of trifluoroethylene, chlorotrifluoroethylene, fluorinated acetylene, and hexafluoropropylene.
[0135] Optionally, the copolymer of the vinylidene fluoride monomer and other monomers may include, but is not limited to, one or more of a vinylidene fluoride-trifluoroethylene copolymer (abbreviated as P(VDF-TrFE)), a vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene copolymer (abbreviated as P(VDF-TrFE-CFE)), a vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene-fluorinated acetylene copolymer (abbreviated as P(VDF-TrFE-CFE-FA)), and a vinylidene fluoride-hexafluoropropylene copolymer (abbreviated as P(VDF-HFP)).
[0136] In some embodiments, the volume distribution particle size Dv50 of the ferroelectric polymer may be 10 nm-150 nm, and may be optionally 15 nm-50 nm.
[0137] In some embodiments, the volume distribution particle size Dv50 of the inorganic ferroelectric can be 0.05μm-5μm, and can be optionally 0.1μm-1μm. The volume distribution particle size Dv50 of the inorganic ferroelectric is within the above range, which can make the ferroelectric coating slurry have a suitable viscosity, facilitate coating, and improve the uniformity and consistency of the ferroelectric coating; it can also increase the bonding force between the ferroelectric coating and the porous structure, and reduce the "powder falling" phenomenon; in addition, it can also reduce the pore blocking problem and improve the air permeability and ion transmission characteristics of the isolation membrane.
[0138] In some embodiments, the Curie point temperature of the inorganic ferroelectric may be 110°C - 150°C, and optionally 120°C - 140°C.
[0139] In some embodiments, the inorganic ferroelectric may include, but is not limited to, one or more of perovskite type, tungsten bronze type, bismuth layer type, pyrochlore type, niobate type, and lead barium lithium niobate. Optionally, the inorganic ferroelectric may include the perovskite type.
[0140] Optionally, the perovskite type may have the molecular formula Ba 1-x A x Ti 1-y B y O3. A may include, but is not limited to, a combination of one or more of Bi, Pb, Sr, Ca, K, Na, and Cd, and B may include, but is not limited to, a combination of one or more of Fe, Sn, Hf, Zr, Ce, Nb, and Th, where 0 ≤ x ≤ 1 and 0 ≤ y ≤ 1.
[0141] Optionally, the perovskite type may include, but is not limited to, barium titanate (BaTiO3), Ba 1-x1 Sr x1 TiO3 (0 ≤ x1 ≤ 1), SrTiO3, PbTiO3, BiFeO3, PbZr y1 Ti 1-y1 O3 (0 ≤ y1 ≤ 1), BaZr y2 Ti 1-y2 O3 (0 < y2 < 1), or one or more of these.
[0142] Optionally, the tungsten bronze type may have the molecular formula M z WO3. M may include, but is not limited to, one or more of Na, K, Rb, and Cs, where 0 < z < 1.
[0143] Optionally, the tungsten bronze type may include, but is not limited to, Na z1 WO3 (0 < z1 < 1), K z2 WO3 (0 < z2 < 1), or one or more of these.
[0144] Optionally, the bismuth layer type may have the molecular formula (Bi2O2)(C n-1 D n O 3n+1 )). C may include, but is not limited to, one or more of Na, K, Ba, Sr, Pb, Ca, Ln, and Bi, and D may include, but is not limited to, one or more of Zr, Cr, Nb, Ta, Mo, W, Fe, Ti, and V, where 2 ≤ n ≤ 5.
[0145] Alternatively, the bismuth layered type may include but is not limited to SrBi2Nb2O9, SrBi2Ta2O9, SrBi2Nb2O9, Bi4Ti3O 12 One or more of .
[0146] Optionally, the pyrochlore type may include but is not limited to one or more of lead metaniobate (PbNb2O6), Cd2Nb2O7.
[0147] Optionally, the niobate type may include but is not limited to one or more of LiNbO3, KNbO3, and NaNbO3.
[0148] In some embodiments, the thickness of the ferroelectric coating may be 1 μm-3.5 μm, and may be 1.5 μm-3 μm. This allows the battery to have high reliability, high coulombic efficiency, and good rate performance.
[0149] In some embodiments, the surface density of the ferroelectric coating may be 2.5 g / m 2 -15g / m 2 , optional 3g / m 2 -12g / m 2 This allows the battery to have high reliability, high coulombic efficiency and good rate performance.
[0150] In some embodiments, the ferroelectric coating may further include a dispersant.
[0151] Alternatively, the dispersant may include, but is not limited to, one or more of hydrolyzed polymaleic anhydride, polyacrylic acid, acrylic acid block copolymers, polyester block copolymers, polyethylene glycol type polyols, polyethylene imine, and their respective derivatives. Derivatives generally refer to products derived from the substitution of hydrogen atoms or atomic groups in a polymer by other atoms or atomic groups.
[0152] Optionally, the ratio of the total weight of the ferroelectric material to the weight of the dispersant may be 1:(0.01-0.02), or optionally 1:(0.010-0.015).
[0153] An appropriate amount of dispersant can make the ferroelectric coating slurry dispersed evenly, facilitate coating, and also help to increase the film weight of the ferroelectric coating.
[0154] In some embodiments, the ferroelectric coating may further include a thickener.
[0155] Optionally, the thickener may include, but is not limited to, one or more of sodium hydroxymethylcellulose, methylcellulose, hydroxyethylcellulose, hydroxypropylmethylcellulose, polyacrylate, polyurethane, and polyether.
[0156] Optionally, the ratio of the total weight of the ferroelectric material to the weight of the thickener may be 1:(0.01-0.02), or optionally 1:(0.010-0.015).
[0157] An appropriate amount of thickener can improve the stability of the ferroelectric coating slurry, facilitate coating, and also help to increase the film weight of the ferroelectric coating.
[0158] The ferroelectric coating 102 is disposed on at least one surface of the porous substrate 101. Figure 6 As shown, the ferroelectric coating 102 may be located on one surface of the porous substrate 101; in some embodiments, such as Figure 7 As shown, the ferroelectric coating 102 may also be located on both surfaces of the porous substrate 101 .
[0159] In some embodiments, Figure 8 As shown, the ferroelectric coating 102 is located on one surface of the porous substrate 101, and a ceramic coating 103 may be provided on another surface of the porous substrate 101. When used in a battery, the ferroelectric coating 102 may face the negative electrode, and the ceramic coating 103 may face the positive electrode.
[0160] In some embodiments, the thickness of the porous substrate may be 4 μm to 15 μm, and optionally 5 μm to 10 μm.
[0161] In some embodiments, the porous substrate may include, but is not limited to, one or more of polyolefins (e.g., polyethylene, polypropylene, etc.), halogenated polyolefins (e.g., polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride, etc.), polyamides, polyesters (e.g., polyethylene terephthalate, etc.), and their respective derivatives. Derivatives generally refer to products derived from the substitution of hydrogen atoms or atomic groups in a polymer by other atoms or atomic groups.
[0162] [Method for preparing isolation film]
[0163] An embodiment of the present application also provides a method for preparing an isolation film.
[0164] The preparation method comprises the following steps: providing a porous substrate; providing a ferroelectric coating slurry: dispersing a ferroelectric material into a solvent to obtain a ferroelectric coating slurry; coating: coating the ferroelectric coating slurry on at least one surface of the porous substrate, and obtaining an isolation film after drying.
[0165] In some embodiments, the drying temperature of the ferroelectric coating slurry may be 60° C.-80° C., and the drying time may be 5 min-30 min.
[0166] In some embodiments, the coating method of the ferroelectric coating slurry may include but is not limited to gravure transfer coating, spin spray coating, dip coating, blade coating, etc.
[0167] In some embodiments, the solvent in the ferroelectric coating slurry may include but is not limited to one or more of deionized water, N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), N,N-dimethylacetamide (DMAC), and tetrahydrofuran (THF).
[0168] In some embodiments, the solid content of the ferroelectric coating slurry may be 25%-45%, and optionally 30%-40%, which is beneficial for coating.
[0169] In some embodiments, the ferroelectric coating slurry may further include one or more of a dispersant and a thickener.
[0170] In some embodiments, the step of providing a ferroelectric coating slurry may include the following steps: dispersing the ferroelectric material, dispersant and solvent once to obtain a primary dispersion solution; adding a thickener to the primary dispersion solution for secondary dispersion to obtain a ferroelectric coating slurry.
[0171] Optionally, the primary dispersion process may be ultrasonic dispersion, and stirring may be performed during the ultrasonic dispersion process. Optionally, the stirring speed during the ultrasonic dispersion process may be 700 rpm-1200 rpm, and the ultrasonic dispersion time may be 30 min-60 min.
[0172] Optionally, the secondary dispersion process may be ultrasonic dispersion, and stirring may be performed during the ultrasonic dispersion process. Optionally, the stirring speed during the ultrasonic dispersion process may be 1000 rpm-1600 rpm, and the ultrasonic dispersion time may be 30 min-90 min.
[0173] In some embodiments, the method for preparing the isolation film may further include the steps of: providing a ferroelectric material; stirring and dispersing the ferroelectric polymer and the first solvent evenly to obtain a clear solution; adding an inorganic ferroelectric to the obtained clear solution and stirring and dispersing the solution evenly to obtain a slurry; and subjecting the obtained slurry to a drying process to obtain a ferroelectric material.
[0174] Alternatively, the first solvent may include anhydrous ethanol, N-methylpyrrolidone (NMP), or the like.
[0175] Optionally, after the ferroelectric polymer and the first solvent are stirred uniformly, ultrasonic dispersion may be performed, and the ultrasonic dispersion time may be 20 min-60 min.
[0176] Optionally, after adding the inorganic ferroelectric to the obtained clear solution and stirring evenly, ultrasonic dispersion can be performed. The ultrasonic dispersion time can be 30 min-60 min.
[0177] Optionally, the slurry can be dried in a drying oven at a drying temperature of 75°C-95°C.
[0178] Optionally, the method for preparing the isolation film may further include the step of grinding the obtained ferroelectric material.
[0179] In some embodiments, the method for preparing the isolation film may further include the steps of: preparing a ceramic coating slurry, and coating the ceramic coating slurry on the surface of the porous substrate where the ferroelectric coating is not provided.
[0180] Some parameters such as raw materials and their contents used in the preparation method of the isolation film provided in the embodiments of the present application can refer to the isolation film provided in the embodiments of the present application, and will not be repeated here.
[0181] Unless otherwise specified, all raw materials used in the method for preparing the isolation membrane can be obtained commercially.
[0182] [Positive electrode]
[0183] The structure and composition of the positive electrode plate can be selected according to the type of battery cell, and the embodiments of the present application are not limited to this.
[0184] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector and including a positive electrode active material. For example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0185] When the battery is a lithium battery, the positive electrode active material includes a material capable of extracting and embedding lithium. As an example, the positive electrode active material may include, but is not limited to, one or more of lithium transition metal oxides, metal chalcogenides, lithium-containing phosphates, and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium titanium oxide, and their respective modified compounds. Lithium transition metal oxides may include, but are not limited to, layered structures and spinel structures. Examples of lithium-containing phosphates may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds.
[0186] In some embodiments, in order to further improve the energy density of the battery, the positive electrode active material may include a general formula of Li a Ni b Co c M d O e D fOne or more of lithium transition metal oxides and modified compounds thereof. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M may include but is not limited to one or more of Ge, Mo, Sn, Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and D may include but is not limited to one or more of N, F, S and Cl.
[0187] In some embodiments, the positive electrode active material may include both lithium transition metal oxide and lithium-containing phosphate, thereby facilitating obtaining a battery having both large capacity and high reliability.
[0188] As an example, the positive electrode active material may include but is not limited to LiCoO2, LiNiO2, LiMnO2, LiNi 1 / 2 Mn 1 / 2O2, LiMn2O4, Li 4 / 3 Ti 5 / 3 O4、LiNi 1 / 2 Mn 1 / 2 O2、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 O2, LiFePO4, LiMnPO4, Li 1.13 Ti 0.57 Fe 0.3 One or more of S2.
[0189] When the battery is a sodium battery, the positive electrode active material includes a material capable of extracting and embedding sodium. As an example, the positive electrode active material may be one or more of a layered transition metal oxide (including but not limited to P2 type, O3 type, etc.), a polyanion material (such as phosphate, fluorophosphate, pyrophosphate, sulfate, etc.), and a Prussian material.
[0190] In some embodiments, as examples, the positive electrode active material may include but is not limited to NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, Na0.67 MO2 (M includes at least two of Fe, Co, Cr, Mn, Ni, V, Ti, and Mo), NaMO2 (M includes at least two of Fe, Co, Ni, V, Ti, and Mo), NaFePO4, NaMnPO4, NaCoPO4, Na4Fe3(PO4)2O7, Na3V2(PO4)2F3, Na3V2(PO4)3, Prussian blue, Prussian white, and one or more of their respective modified compounds.
[0191] The modified compounds of the above-mentioned positive electrode active materials may be the ones that undergo doping modification and / or surface coating modification on the positive electrode active materials.
[0192] In some embodiments, the positive electrode film layer may also optionally include a positive electrode conductive agent. As an example, the positive electrode conductive agent may include, but is not limited to, one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0193] In some embodiments, the positive electrode film layer may also optionally include a positive electrode binder. As an example, the positive electrode binder may include, but is not limited to, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorinated acrylic resin, styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS) One or more.
[0194] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include, but is not limited to, one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may include, but is not limited to, one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0195] The positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, the optional positive electrode conductive agent, the optional positive electrode binder and any other components in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.
[0196] [Negative electrode]
[0197] The battery cell includes a negative electrode plate. The structure and composition of the negative electrode plate can be selected according to the type of the battery cell, and the embodiment of the present application is not limited to this.
[0198] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0199] The negative electrode active material may adopt materials known in the art. As an example, the negative electrode active material may include, but is not limited to, one or more of carbon-based materials, silicon-based materials, tin-based materials, and lithium titanate. Carbon-based materials may include, but are not limited to, one or more of natural graphite, artificial graphite, soft carbon, hard carbon, pyrolytic carbon, coke, glassy carbon, sintered bodies of organic polymer compounds, and mesophase carbon microbeads. Silicon-based materials may include, but are not limited to, one or more of elemental silicon, silicon oxide, silicon-carbon composites, silicon-nitrogen composites, and silicon alloy materials. Tin-based materials may include, but are not limited to, one or more of elemental tin, tin oxide, and tin alloy materials.
[0200] In some embodiments, the negative electrode film layer may further optionally include a negative electrode conductive agent. As an example, the negative electrode conductive agent may include but is not limited to one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0201] In some embodiments, the negative electrode film layer may further optionally include a negative electrode binder. As an example, the negative electrode binder may include, butadiene styrene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS) One or more.
[0202] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC), a PTC thermistor material, and the like.
[0203] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.
[0204] The negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate may also include a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode plate may also include a protective layer covering the surface of the negative electrode film layer.
[0205] In some embodiments, the negative electrode plate may include a negative electrode current collector and a metal layer disposed on at least one surface of the negative electrode current collector, and the metal material in the metal layer may include but is not limited to one or more of lithium, lithium alloy, sodium, and sodium alloy.
[0206] Lithium alloys may be alloys formed by metallic lithium and other metallic elements or non-metallic elements. As an example, other metallic elements in lithium alloys may include, but are not limited to, one or more of tin, zinc, aluminum, magnesium, silver, gold, gallium, indium, and platinum, and non-metallic elements in lithium alloys may include one or more of boron, carbon, and silicon.
[0207] The sodium alloy may be an alloy formed by metallic sodium and other metallic elements or non-metallic elements. As an example, the other metallic elements in the sodium alloy may include, but are not limited to, one or more of tin, zinc, aluminum, magnesium, silver, gold, gallium, indium, and platinum, and the non-metallic elements in the sodium alloy may include one or more of boron, carbon, and silicon.
[0208] In some embodiments, the negative electrode plate may be a lithium sheet (foil), a lithium alloy sheet (foil), a sodium sheet (foil) or a sodium alloy sheet (foil).
[0209] In some embodiments, the negative electrode sheet may include a negative electrode current collector to be assembled into a negative electrode-free battery cell.
[0210] In some embodiments, the negative electrode current collector may include, but is not limited to, one or more of a metal foil, a metal foam current collector, a metal mesh current collector, a carbon felt current collector, a carbon cloth current collector, a carbon paper current collector, and a composite current collector.
[0211] Examples of metal foil materials include copper foil, copper alloy foil, nickel foil, nickel alloy foil, aluminum foil, and aluminum alloy foil. Examples of metal foam current collectors include foam copper, foam nickel, and foam aluminum. Examples of metal mesh current collectors include copper mesh, nickel mesh, and aluminum mesh.
[0212] The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include, but is not limited to, one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, aluminum, aluminum alloy, silver and silver alloy. As an example, the polymer material base layer may include, but is not limited to, one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0213] [Electrolytes]
[0214] The battery cell includes an electrolyte. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can include one or more selected from solid electrolytes and liquid electrolytes (ie, electrolytes).
[0215] In some embodiments, the electrolyte is an electrolyte solution including an electrolyte salt and an organic solvent.
[0216] The electrolyte salt may include phosphates, perchlorates, organic boron salts, fluorine-containing organic salts, imide salts, and the like.
[0217] When the battery is a lithium battery, as an example, the electrolyte salt may include, but is not limited to, one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0218] When the battery is a sodium battery, as an example, the electrolyte salt may include, but is not limited to, sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP), and sodium tetrafluorooxalatophosphate.
[0219] In some embodiments, the concentration of the electrolyte salt may be greater than 0.3 mol / L, and may be greater than 0.7 mol / L. The concentration of the electrolyte salt may further be less than 4 mol / L, and may be less than 2.5 mol / L or less than 1.7 mol / L.
[0220] Organic solvents may include, but are not limited to, one or more of esters, ethers, sulfones, nitriles, etc. Esters may include, but are not limited to, one or more of carbonates, phosphates, carboxylates, sulfates, sulfonates, etc. Carbonates may include cyclic carbonates and / or linear carbonates. Linear carbonates may include low-viscosity polar linear carbonates, aliphatic branched-chain carbonates, etc.
[0221] As an example, the organic solvent may include, but is not limited to, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), diethyl sulfone (ESE), tetraethylene glycol dimethyl ether (TEGDME), ethylene glycol dimethyl ether (DME), 1,3-dioxolane (DOL), trimethyl phosphate, 3-methoxypropionitrile, H(CF2)2OCH3, C4F9O CH3, H(CF2)2OCH2CH3, H(CF2)2OCH2CF3, H(CF2)2CH2O(CF2)2H, CF3CHFCF2OCH3, CF3CHFCF2OCH2CH3, 2-trifluoromethylhexafluoropropylmethyl ether, 2-trifluoromethylhexafluoropropylethyl ether, 2-trifluoromethylhexafluoropropylpropyl ether, 3-trifluoromethyloctafluorobutylmethyl ether, 3-trifluoromethyloctafluorobutylethyl ether, 4-trifluoromethyl The invention further comprises one or more of trifluoromethyl decafluoropentyl methyl ether, 4-trifluoromethyl decafluoropentyl ethyl ether, 4-trifluoromethyl decafluoropentyl propyl ether, 5-trifluoromethyl dodecafluorohexyl methyl ether, 5-trifluoromethyl dodecafluorohexyl ethyl ether, 5-trifluoromethyl dodecafluorohexyl propyl ether, 6-trifluoromethyl tetradecafluoroheptyl methyl ether, 6-trifluoromethyl tetradecafluoroheptyl ethyl ether, 6-trifluoromethyl tetradecafluoroheptyl propyl ether, 7-trifluoromethyl hexadecafluorooctyl methyl ether, 7-trifluoromethyl hexadecafluorooctyl ethyl ether, and 7-trifluoromethyl hexadecafluorooctyl propyl ether.
[0222] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature power performance.
[0223] The preparation method of battery cells is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the above-mentioned electrolyte is injected after drying. After vacuum packaging, standing, formation and other processes, a battery cell is obtained. Multiple battery cells can also be further connected in series, in parallel or in mixed connection to form a battery module. Multiple battery modules can also be connected in series, in parallel or in mixed connection to form a battery pack. In some embodiments, multiple battery cells can also directly form a battery pack.
[0224] The present application also provides an electrical device, which includes a battery provided in the present application. The battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0225] The electric device can select the type of battery according to its usage requirements, such as a battery cell, a battery module or a battery pack.
[0226] Fig. 9 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.
[0227] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.
[0228] Example
[0229] The following examples describe the disclosure of the present application in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present application are apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0230] Example 1
[0231] Weigh barium titanate (BaTiO3) powder and ferroelectric polymer powder, the weight ratio of the two is 90:10. The barium titanate powder is a tetragonal phase, the volume distribution particle size Dv50 is 0.3μm, and the dielectric constant ε r 5460. Ferroelectric polymer PVDF, in which the β phase content is 90%, the crystallinity is 65%, and the dielectric constant ε r The molecular weight is 9.6, the melting point is 150°C, and the weight average molecular weight is 540,000.
[0232] After mixing the ferroelectric polymer powder and anhydrous ethanol, the mixture is placed in an ultrasonic machine for ultrasonic dispersion for 35-45 minutes to obtain a clear solution. After adding the barium titanate powder to the clear solution and shaking it evenly, the mixture is placed in an ultrasonic machine for ultrasonic dispersion for 45-50 minutes to obtain a slurry. The slurry is placed in a drying oven and dried at 90°C, and the dried powder is placed in a mortar and ground into a fine powder to obtain a ferroelectric material powder.
[0233] The obtained ferroelectric material powder is uniformly dispersed in NMP, and hydrolyzed polymaleic anhydride is added for ultrasonic dispersion. After ultrasonic dispersion for 2 hours, sodium hydroxymethyl cellulose is added for secondary dispersion to obtain a ferroelectric coating slurry with a solid content of about 35%. In the ferroelectric coating slurry, the weight ratio of the ferroelectric material, hydrolyzed polymaleic anhydride, and sodium hydroxymethyl cellulose is 1:0.01:0.01.
[0234] The obtained ferroelectric coating slurry was coated on one surface of a PE porous substrate with a porosity of 50% and a thickness of 9 μm by gravure transfer coating, and then vacuum dried at 60°C to obtain an isolation film. The thickness of the ferroelectric coating was 3 μm and the surface density was 6 g / m 2 .
[0235] Examples 2 to 5
[0236] The preparation method of the isolation film is similar to that of Example 1, except that the β-phase content of the ferroelectric polymer used is different. The specific parameters are shown in Table 1.
[0237] Comparative Example 1
[0238] Alumina powder and polyacrylic acid were uniformly dispersed in NMP at a weight ratio of 90:10 to obtain a ceramic coating slurry. The obtained ceramic coating slurry was coated on one surface of a PE porous substrate with a porosity of 50% and a thickness of 9 μm by gravure transfer coating, and vacuum dried at 60°C to obtain a separator. The thickness of the ceramic coating was 3 μm.
[0239] Comparative Example 2
[0240] The preparation method of the isolation film is similar to that of Example 1, except that ferroelectric polymer is not used, but α-phase polyvinylidene fluoride is used, wherein the α-phase content is more than 75%.
[0241] Comparative Example 3
[0242] The preparation method of the isolation film is similar to that of Example 1, except that the β-phase content of the ferroelectric polymer used is 30%. Specific parameters are shown in Table 1.
[0243] Example 6
[0244] The preparation method of the isolation film is similar to that of Example 1, except that the weight ratio of the barium titanate powder to the ferroelectric polymer powder is 99.5:0.5.
[0245] Example 7
[0246] The preparation method of the isolation film is similar to that of Example 1, except that the weight ratio of the barium titanate powder to the ferroelectric polymer powder is 99:1.
[0247] Example 8
[0248] The preparation method of the isolation film is similar to that of Example 1, except that the weight ratio of the barium titanate powder to the ferroelectric polymer powder is 95:5.
[0249] Example 9
[0250] The preparation method of the isolation film is similar to that of Example 1, except that the weight ratio of the barium titanate powder to the ferroelectric polymer powder is 85:15.
[0251] Example 10
[0252] The preparation method of the isolation film is similar to that of Example 1, except that the weight ratio of the barium titanate powder to the ferroelectric polymer powder is 80:20.
[0253] Embodiment 11
[0254] The preparation method of the isolation film is similar to that of Example 1, except that the weight ratio of the barium titanate powder to the ferroelectric polymer powder is 75:25.
[0255] Example 12
[0256] The preparation method of the isolation film is similar to that of Example 1, except that the volume distribution particle size Dv50 of the barium titanate powder is 5 μm.
[0257] Embodiment 13
[0258] The preparation method of the isolation film is similar to that of Example 1, except that the volume distribution particle size Dv50 of the barium titanate powder is 3 μm.
[0259] Embodiment 14
[0260] The preparation method of the isolation film is similar to that of Example 1, except that the volume distribution particle size Dv50 of the barium titanate powder is 1 μm.
[0261] Embodiment 15
[0262] The preparation method of the isolation film is similar to that of Example 1, except that the volume distribution particle size Dv50 of the barium titanate powder is 0.5 μm.
[0263] Example 16
[0264] The preparation method of the isolation film is similar to that of Example 1, except that the volume distribution particle size Dv50 of the barium titanate powder is 0.1 μm.
[0265] Embodiment 17
[0266] The preparation method of the isolation film is similar to that of Example 1, except that the volume distribution particle size Dv50 of the barium titanate powder is 0.05 μm.
[0267] Embodiment 18
[0268] The preparation method of the isolation film is similar to that of Example 1, except that the thickness of the ferroelectric coating is 1 μm.
[0269] Embodiment 19
[0270] The preparation method of the isolation film is similar to that of Example 1, except that the thickness of the ferroelectric coating is 1.5 μm.
[0271] Embodiment 20
[0272] The preparation method of the isolation film is similar to that of Example 1, except that the thickness of the ferroelectric coating is 3.5 μm.
[0273] Examples 21 to 26
[0274] The preparation method of the isolation film is similar to that of Example 1, except that the types of inorganic ferroelectrics or ferroelectric polymers in the ferroelectric coating are different. Specific parameters are shown in Table 2.
[0275] The inorganic ferroelectric and ferroelectric polymer materials used in the above embodiments and comparative examples are all commercially available.
[0276] Performance Testing
[0277] (1) Puncture strength test of isolation film
[0278] The puncture strength of the isolation film is tested according to GB / T36363-2018.
[0279] Cut the isolation film into samples with a width of 10mm and a length of 150mm, then flatten and clamp them in the fixture, and perform a puncture test with a steel needle at a rate of 100mm / min. After the test, take out the sample, and perform a thickness test at 4 points around the pinhole according to GB / T6672-2001, take the average value and calculate the puncture strength. The diameter of the steel needle can be 1mm, and the radius of the spherical top can be 0.5mm. The surface of the steel needle is smooth, free of rust, oxide layer and oil. During the test, the number of isolation film samples can be more than 6, and the test results are averaged.
[0280] (2) Tensile strength test of isolation film
[0281] The tensile strength of the isolation film in the transverse (TD) and longitudinal (MD) directions is tested according to GB / T36363-2018.
[0282] Cut the separator into samples with a width of 10 mm and a length of 150 mm (the length direction is parallel to the transverse direction of the separator) for testing to obtain the tensile strength in the transverse (TD) direction of the separator. The testing instrument can be a universal tensile testing machine, and the tensile rate can be 50 mm / min. During the test, the number of separator samples can be more than 6, and the test results are averaged.
[0283] Cut the separator into samples with a width of 10 mm and a length of 150 mm (the length direction is parallel to the longitudinal direction of the separator) for testing to obtain the tensile strength in the longitudinal direction (TD) of the separator. The testing instrument can be a universal tensile testing machine, and the tensile rate can be 50 mm / min. During the test, the number of separator samples can be more than 6, and the test results are averaged.
[0284] (3) Thermal shrinkage test of isolation film
[0285] The heat shrinkage of the isolation film in the transverse (TD) and longitudinal (MD) directions is tested according to GB / T36363-2018.
[0286] The width of the isolation film sample is 50 mm and the length is 100 mm. The temperature of the hot box is 105°C and the heat treatment time is 60 minutes. After the completion, the length and width of the isolation film are measured and the values are marked as a and b respectively.
[0287] The longitudinal (MD) heat shrinkage rate = [(100-a) / 100] × 100%, the transverse (TD) heat shrinkage rate = [(50-b) / 50] × 100%. During the test, the number of isolation film samples can be more than 6, and the test results are averaged.
[0288] (4) Air permeability test of isolation film
[0289] The air permeability of the isolation membrane is tested according to GB / T36363-2018.
[0290] The time required for 100 mL of air to pass through the isolation membrane is taken as the air permeability of the isolation membrane. The greater the air permeability of the isolation membrane, the worse the air permeability of the isolation membrane. During the test, the number of isolation membrane samples can be more than 6, and the test results are averaged. The test instrument can be the Kumagai KRK Wangyan air permeability tester.
[0291] (5) Dielectric constant ε of ferroelectric material powder r test
[0292] At 25°C, take an appropriate amount of ferroelectric material powder, cover both sides with aluminum foil, place it in a mold, and use a powder tablet press to press it into a disc with a pressure of 2Mpa and a holding time of 2min. After the pressing is completed, take out the sample disc and use a precision digital bridge instrument to measure the dielectric constant ε in the frequency range of 20Hz-2MHz. r Test. During the test, the number of samples can be more than 6, and the test results are averaged.
[0293] Next, the above-mentioned isolation membranes were assembled into button-type batteries and the rate performance was tested.
[0294] The button cell can be prepared as follows.
[0295] Lithium iron phosphate, conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) were mixed evenly in an appropriate amount of solvent N-methylpyrrolidone (NMP) at a weight ratio of 8:1:1 to obtain a positive electrode slurry; the positive electrode slurry was coated on the positive electrode current collector aluminum foil and dried to obtain a positive electrode plate. In an argon-protected glove box, the positive electrode plate, isolation membrane, and lithium sheet were assembled into a CR2430 button cell. The electrolyte salt of the electrolyte was LiFSI with a concentration of 1 mol / L, and the solvent of the electrolyte was ethylene glycol dimethyl ether.
[0296] The ferroelectric coating layers of the separators of Examples 1 to 26 and Comparative Examples 1 to 3 all faced the lithium sheet.
[0297] At 25°C, the button cell was charged to 3.65V at 0.1C constant current, and then charged to 0.05C at 3.65V constant voltage; after the button cell was left to stand for 10 minutes, it was discharged to 2.5V at 0.1C constant current. After the button cell was cycled twice according to the above method, the following cycle performance test was performed.
[0298] The button cell was charged to 3.65V at 0.5C, 1C, and 2C rates respectively, and then charged to 0.05C at 3.65V; after the button cell was left to stand for 10 minutes, it was discharged to 2.5V at 0.2C constant current to obtain. The button cell was cycled 100 times according to the above method to obtain the charging capacity of the 100th cycle and the discharge capacity of the 100th cycle. The coulomb efficiency of the button cell cycled 100 times = the discharge capacity of the 100th cycle / the charging capacity of the 100th cycle.
[0299] During the test, the number of button cell samples may be more than 6, and the test results shall be averaged.
[0300] The test results are shown in Table 3.
[0301] Table 1
[0302]
[0303] Table 2
[0304]
[0305] Table 3
[0306]
[0307]
[0308] It can be seen from the test results of Examples 1 to 26 and Comparative Examples 1 to 3 that by making the ferroelectric coating of the isolation membrane include an inorganic ferroelectric and a ferroelectric polymer, and the content of β-phase polyvinylidene fluoride in the ferroelectric polymer is greater than or equal to 60%, the coulombic efficiency and rate performance of the battery can be improved without affecting the air permeability, thermal shrinkage and mechanical strength of the isolation membrane. Fig.10 A scanning electron microscope (SEM) image of the isolation film prepared in Example 1 is shown. Fig.10 It can be seen that part of the ferroelectric polymer is dispersed on the surface of the inorganic ferroelectric.
[0309] It can also be seen from the test results of Examples 1 to 5 that the dielectric constant ε of the ferroelectric material can be further improved by further adjusting the content of β-phase polyvinylidene fluoride in the ferroelectric polymer. r , which can further improve the air permeability, thermal shrinkage and mechanical strength of the isolation membrane, and can also further improve the coulombic efficiency and rate performance of the battery.
[0310] It can also be seen from the test results of Examples 6 to 11 that the dielectric constant ε of the ferroelectric material can be further improved by further adjusting the weight ratio of the inorganic ferroelectric and the ferroelectric polymer. r , which can further improve the air permeability, thermal shrinkage and mechanical strength of the isolation membrane, and can also further improve the coulombic efficiency and rate performance of the battery.
[0311] It can also be seen from the test results of Examples 12 to 17 that the dielectric constant ε of the ferroelectric material can be further increased by further adjusting the particle size of the inorganic ferroelectric. r , which can further improve the air permeability, thermal shrinkage and mechanical strength of the isolation membrane, and can also further improve the coulombic efficiency and rate performance of the battery.
[0312] It can also be seen from the test results of Examples 21 to 26 that the dielectric constant ε of the ferroelectric material varies depending on the type of inorganic ferroelectric and / or ferroelectric polymer. r There will be differences, and the improvement effects on the battery coulombic efficiency and rate performance will also be different.
[0313] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. An isolation film comprising a porous substrate and a ferroelectric coating located on at least one surface of the porous substrate, characterized in that: The ferroelectric coating comprises a ferroelectric material, wherein the ferroelectric material comprises an inorganic ferroelectric and a ferroelectric polymer. The ferroelectric polymer includes polyvinylidene fluoride and copolymers thereof. The ferroelectric polymer includes β-phase polyvinylidene fluoride, and the content of β-phase polyvinylidene fluoride in the ferroelectric polymer is greater than or equal to 60%.
2. The isolation film according to claim 1, characterized in that: The content of β-phase polyvinylidene fluoride in the ferroelectric polymer is greater than or equal to 80%, and can be optionally greater than or equal to 90%.
3. The isolation film according to any one of claims 1 to 2, characterized in that: The dielectric constant ε of the ferroelectric coating r Greater than the dielectric constant ε of the inorganic ferroelectric r Optionally, the dielectric constant ε of the ferroelectric coating is r The dielectric constant ε of the inorganic ferroelectric r The ratio is greater than or equal to 1.6, and can be greater than or equal to 2.0; The dielectric constant ε of the inorganic ferroelectric r Greater than the dielectric constant ε of the ferroelectric polymer r .
4. The isolation membrane according to any one of claims 1 to 3, characterized in that: The dielectric constant ε of the inorganic ferroelectric r 200-8000, optionally 2000-6000; and / or, The dielectric constant ε of the ferroelectric polymer r 5-100, optional 8-70.
5. The isolation film according to any one of claims 1 to 4, characterized in that: At least a portion of the ferroelectric polymer is located on at least a portion of the surface of the inorganic ferroelectric.
6. The isolation film according to any one of claims 1 to 5, characterized in that: The weight content of the inorganic ferroelectric in the ferroelectric material is 80%-99%, optionally 85%-95%; and / or, The weight content of the ferroelectric polymer in the ferroelectric material is 1%-20%, and optionally 5%-15%.
7. The isolation membrane according to any one of claims 1 to 6, characterized in that: The ferroelectric polymer satisfies at least one of the following conditions (1) to (5): (1) The Curie point temperature of the ferroelectric polymer is 150°C-250°C, and can be optionally 160°C-200°C; (2) The residual polarization intensity of the ferroelectric polymer is 10 mC / m 2 -1000mC / m 2 , optional 20mC / m 2 -800mC / m 2 ; (3) The weight average molecular weight of the ferroelectric polymer is 200,000-800,000, and can be 400,000-650,000; (4) The melting temperature of the ferroelectric polymer is 140°C-220°C, and can be optionally 143°C-200°C; (5) The crystallinity of the ferroelectric polymer is greater than or equal to 45%, and can be optionally 45%-68%.
8. The isolation membrane according to any one of claims 1 to 7, characterized in that: The Curie point temperature of the inorganic ferroelectric is 110°C-150°C, and can be optionally 120°C-140°C.
9. The isolation film according to any one of claims 1 to 8, characterized in that: The ferroelectric polymer includes one or more of polyvinylidene fluoride, a copolymer of a vinylidene fluoride monomer and other monomers; Optionally, the other monomers include one or more of trifluoroethylene, chlorotrifluoroethylene, fluorinated acetylene, and hexafluoropropylene. Optionally, the copolymer of the vinylidene fluoride monomer and other monomers includes one or more of vinylidene fluoride-trifluoroethylene copolymer, vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene copolymer, vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene-fluorinated acetylene copolymer, and vinylidene fluoride-hexafluoropropylene copolymer.
10. The isolation film according to any one of claims 1 to 9, characterized in that: The inorganic ferroelectric includes one or more of perovskite type, tungsten bronze type, bismuth layered type, pyrochlore type, niobate type and lead barium lithium niobate.
11. The isolation film according to any one of claims 1 to 10, characterized in that: The volume distribution particle size Dv50 of the inorganic ferroelectric is 0.05 μm-5 μm, and can be optionally 0.1 μm-1 μm; and / or, The volume distribution particle size Dv50 of the ferroelectric polymer is 10nm-150nm, and can be optionally 15nm-50nm.
12. The isolation film according to any one of claims 1 to 11, characterized in that: The thickness of the ferroelectric coating is 1 μm-3.5 μm, and can be 1.5 μm-3 μm; and / or, The surface density of the ferroelectric coating is 2.5 g / m 2 -15g / m 2 , optional 3g / m 2 -12g / m 2 .
13. The isolation membrane according to any one of claims 1 to 12, characterized in that: The ferroelectric coating further comprises a dispersant and / or a thickener, Optionally, the dispersant includes one or more of hydrolyzed polymaleic anhydride, polyacrylic acid, acrylic acid block copolymer, polyester block copolymer, polyethylene glycol type polyol, polyethylene imine, and their respective derivatives; Optionally, the ratio of the total weight of the ferroelectric material to the weight of the dispersant is 1:(0.01-0.02), optionally 1:(0.010-0.015); Optionally, the thickener includes one or more of sodium hydroxymethylcellulose, methylcellulose, hydroxyethylcellulose, hydroxypropyl methylcellulose, polyacrylate, polyurethane, and polyether; Optionally, the ratio of the total weight of the ferroelectric material to the weight of the thickener is 1:(0.01-0.02), and optionally 1:(0.010-0.015).
14. The isolation membrane according to any one of claims 1 to 13, characterized in that: The ferroelectric coating is located on one surface of the porous substrate, and a ceramic coating is arranged on the other surface of the porous substrate. When used in a battery, the ferroelectric coating faces the negative electrode, and the ceramic coating faces the positive electrode.
15. The isolation membrane according to any one of claims 1 to 14, characterized in that: The thickness of the porous substrate is 4 μm-15 μm, and can be 5 μm-10 μm; and / or, The porous substrate includes one or more of polyolefins, halogenated polyolefins, polyamides, polyesters, and their respective derivatives.
16. A battery cell, characterized in that: The isolation film comprises the isolation film according to any one of claims 1 to 15.
17. A battery, characterized in that: Comprising the battery cell as claimed in claim 16.
18. An electrical device, characterized in that: Comprising the battery of claim 17.
Citation Information
Patent Citations
Improved battery separators and related methods
CN108140787A
Lithium-sulfur battery diaphragm and application
CN115207560A
Secondary battery and electric device
CN115911757A
Graft polymer, preparation method, binder, positive pole piece, secondary battery and electric device
CN116355147A
Battery, electronic equipment and processing method of diaphragm
CN116706426A
Cited By
Separator, battery cell, battery, and electric device
EP4625667A1